2019
DOI: 10.1039/c9ob02007a
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterisation of the structure and radical scavenging potency of Pu'Er tea () polyphenol theaflavin

Abstract: Resolving the functional 3D structural poses of Pu'Er tea antioxidant theaflavin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Like EGCG, theaflavins can stimulate Aβ and α nuclide (αS) to assemble non-toxic spherical polymers, and are effective inhibitors of Aβ and αS fiber formation. Mechanism studies have shown that theaflavins have a stronger conjugation effect and phenol-qhinone balance structure than catechins, leading to stronger proton supply and nucleophilicity, which is essential to inhibit the aggregation of Aβ [65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Like EGCG, theaflavins can stimulate Aβ and α nuclide (αS) to assemble non-toxic spherical polymers, and are effective inhibitors of Aβ and αS fiber formation. Mechanism studies have shown that theaflavins have a stronger conjugation effect and phenol-qhinone balance structure than catechins, leading to stronger proton supply and nucleophilicity, which is essential to inhibit the aggregation of Aβ [65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…33 A systematic approach of indexing and accounting for the contributions of each molecular component and their individual degrees of freedom allows one to more effectively generate a non-degenerate set of topologically possible conformations ( poses) towards resolving the structurally probable set. Such an approach has been successfully implemented for peptides, 34 lipids, 35,36 anti-oxidants, 37,38 bioactive molecules, [39][40][41][42] antibiotics 43 and relevant polyphenols. 44 Each manifests their own unique set of conformational poses, stabilised by unique intramolecular interactions 45 and systemic energy management.…”
Section: Papermentioning
confidence: 99%
“…The strong antioxidant activity of theaflavins gives them unique physiological functions. The diversity of the theaflavin structure is mainly caused by the changes in its 9-OH group, and its structural preference is regulated by its unique fused bicyclic benzotropolone part and its flatness . It can be seen from Figure that the benzophenone ring structure formed by the two B rings may be the preferred oxidation position of TF.…”
Section: Physicochemical Properties and Biosynthesis Of Theaflavinsmentioning
confidence: 99%
“…The diversity of the theaflavin structure is mainly caused by the changes in its 9-OH group, and its structural preference is regulated by its unique fused bicyclic benzotropolone part and its flatness. 67 It can be seen from Figure 1 that the benzophenone ring structure formed by the two B rings may be the preferred oxidation position of TF. They are considered to be the basis of theaflavin's superior ability to scavenge free radicals and neutralize reactive oxygen species (ROS).…”
Section: ■ Introductionmentioning
confidence: 99%